Uporaba satelitskih posnetkov SPOT za izdelavo ortopodob : Application of SPOT satellite imagery for orthoimage generation - Aleš Marsetič; Krištof Oštir (Geodetski Vestnik, 2007)
In the article, the application of stereopairs of panchromatic and multispectral SPOT satellite imagery in photogrammetric applications is presented. Theoretical basis of the generation of digital elevation models and orthoimages and a description of the practical processing of orthoimages are given. Examined are the possibilities of the application of the middle-resolution images from mountainousregions. The accuracy of the orthoimages has been determined by comparing with orthophotos DOF 5. The results are unexpectedly good and show the potential of SPOT imagery. The accuracy of the resultshas been, in addition to the input data, affected by the restrictions of the digital, automatic processing techniques in the software applied.